SOEs Legal Regime of After the 2025 Law: Status on State Finance and State Administration - Bagus Satrio Utomo (CV. ULIL ALBAB CORP, 2026)
Indonesian State-Owned Enterprises (SOEs/BUMN) have historically operated within a legal framework containing a conflict between public and private law. This dualism exposes executives to criminalization risk for ordinary business losses. This study examines the cumulative 2025 legislative reforms, culminating in Law (UU) Number 16 of 2025 (The Fourth Amendment to the BUMN Law), to assess its effectiveness in resolving this legal dualism. The new law introduces a radical separation of regulator (BP BUMN) and operator (Danantara) functions. It legally redefines BUMN assets as corporate property (Article 4A(5)) and stipulates that an BUMN's loss is not a